Cómo crear ediciones digitales académicas entre La Habana y Berlín. El caso de Proyecto Humboldt Digital (ProHD) - Antonio Rojas-Castro; Grisel Terrón Quintero; Alaina Solernou Ferrer; Tobias Kraft (Journal of the Text Encoding Initiative)
Studies on the Prussian writer and naturalist Alexander von Humboldt and editions of his work are abundant. Among the many outstanding chapters of his famous journey through the American tropics, the two visits to Cuba (1800–1801/1804) stand out as a particular case. To this day very few original documents are known about his actual visits, the colonial sources that informed him and the history of his reception. This is due, in large part, to the fact that documentary sources are difficult to access. To overcome this difficulty, the Project Humboldt Digital was born in 2019, a cooperation project carried out between Havana and Berlin, whose main objective is to publish a collection of texts related to Humboldt’s stay in Cuba. In this article we aim to explain how our digital scholarly editions have been created from a methodological point of view. After outlining the origins, we present the workflow developed between the Oficina del Historiador de la Ciudad de La Habana and the Berlin-Brandenburg Academy of Sciences and Humanities to digitize, describe, publish, edit and preserve in digital format a collection of previously selected texts. Also, we describe the model of data representation in TEI format, as well as the tools employed to encode and publish the editions. Finally, we analyze the first editorial results obtained and offer some conclusions on the main challenges faced.